Development Of An Affordable Curemeter To Monitor Cure Characteristics Of Unsaturated Polyester Resin - Mad Naser, Mohamad Azwan (2019)
The objective of this study was to develop an affordable curemeter equipped with a real-time monitoring software and assess its potential as a rheological testing instrument to study the rheological properties and behaviour of thermoset polymer. A newly fabricated curemeter with an oscillation shearing movement was developed. A few modifications were made on the original design to suit the current (torque) and speed sensor systems requirement. Real-time monitoring software was also developed together with the newly fabricated curemeter as a supporting system to analyze rheological behaviour of a thermoset polymer. Data generated by the newly fabricated curemeter system were compared with data obtained from commercial oscillatory rheometer (Anton Parr model MCR 301). Repeatability test was carried out to measure the level of reliability of the recorded data by using coefficient of variance analysis. In order to study the cure characteristics of a thermoset polymer, evaluation on the effect of hardener content in unsaturated polyester resin was carried out by using this newly fabricated curemeter. The obtained data trend were quite reliable and able to match with the data trend generated by the commercial rheometer. It was found that the newly fabricated curemeter has big potential as a device to monitor the cure characteristics and rheological behaviour of a thermoset polymer.